Stefan Balei’s Psychological-Pedagogical Inheritance in the Foreign and Native Scientific Discourse - Fanenshtel, Nataliia (Pedagogical Discourse, 2015)
Historiografic analysis of Stefan Balei’s creative inheritance has been done in the article. On the basis of analytical-synthetic approach the author systematized scientific researches, and as a result the branches of sciences were determined, in which the research was made. It is found out that the foreign scientists, specifically from Poland, research mostly Balei’s separate achievements in general psychology, еducational psychology, psychology of creation, philosophy and pedagogiсs. The first attempt to study and reconstruct scientist’s inheritance systematically has been realized by Ukrainian philosopher M.Vernikov and continued by his followers. The analysis of scientific literature has shown that Balei’s scientific approach is insufficiently represented in the native pedagogical science. This demands further thorough study of his scientific works.